Process evaluation of dialectical behavior therapy dissemination: Knowledge retention and recursive training effects - Holbrook, Amber M.; Hunt, Susan R.; See, Mary Renata (Current psychology (New Brunswick, N.J.), 2022)
Dialectical behavior therapy (DBT) can be challenging to implement with fidelity to the model. Residential treatment settings are frequently overlooked as sites of implementation for DBT despite the potential benefits. This mixed-methods process evaluation examines the impact of DBT training in five residential programs on provider DBT-specific knowledge, staff turnover rates, and staff perceptions of training impact on their practice. Post-training staff knowledge levels varied considerably, but on average demonstrated substantial DBT-related knowledge retention. Staff turnover rates did not change significantly in four of five programs despite showing an overall trend in reduction. Qualitative results suggest substantial recursive training effects consistent with the DBT model. Themes emerged related to the impact of the training on effectiveness of practice with clients, application of DBT skills in staff personal lives, and positive effects on program culture. Results have implications for better understanding the mechanisms of successful dissemination of DBT across treatment settings.